PERAN ASET DAN PROSES DALAM PEMBENTUKAN KINERJA DAYA SAING UKM SEPATU DI SURABAYA - Andhy Setyawan; Henrycus Winarto Santoso (Universitas Trunojoyo Madura, 2016)
Small and medium enterprises (SMEs) have an important role and strategic development. A healthy growth of SMEs will be a competitive advantage for developing countries to be able to survive and move forward in the competitive dynamics in the era of globalization. This study aims to examine the performance of the competitiveness of SMEs shoes on the Surabaya region through Asset approach - Process - Performance (APK). Based on the results of the regression analysis, found that the positive effect of SME assets in process, and the process is also a positive effect on performance.